Muslim Nahdlatul Ulama (NU) Intellectuals and the Environment: Ulil Abshar Abdalla’s Critique of the ‘Wahabi Lingkungan’ Thought - Mursalat (LAKPESDAM MWCNU Palengaan, 2025)
This study analyzes Ulil Absha Abdallah's ideas on environmental moderation and critiques the less contextual “Wahabi Lingkungan” approach. Employing a qualitative method with netnography design, the research draws on digital data to explore social, cultural, and ideological phenomena. Results reveal that Ulil's critique, as an NU thinker, targets